Increasing Teacher Professionalism Through Change Management in Madrasah: Kurt Lewin's Perspective - Mahmud, Muchammad Eka; Baharun, Hasan; Asykur, Muamar; Rochmatin, Zulfa (Southeast Asian Journal of Islamic Education, 2022)
This paper describes the efforts of Madrasah Ibtidaiyah in increasing teacher professionalism in the digital era through the Kurt Lewin model of change management. A digital era is a form of change, and for this reason, teachers who can also adapt to existing changes are needed. One of the competencies that must be possessed by the teachers is the ability to use ICT. Lewin's change management model identified three stages toward change: unfreeze, change, and refreeze. The analogy of these stages is the process of ice blocks to be reformed as desired; it needs to be melted first (unfreeze), then put into molds according to the desired shape (change) and refrozen (refreeze) into different blocks. The researcher conducted interviews with several informants at MI Mambaul Ulum to obtain valid and accountable data using a purposive sampling technique. Data analysis was carried out through data collection, data condensation, data display, and data verification/conclusion.The research results obtained are first, the forms of the unfreeze stages at MI Mambaul Ulum, namely needs analysis, implementing EDM and RKAM, comparative studies and forming the structure of the madrasah. Second, the forms of the change stages at MI Mambaul Ulum are providing opportunities for further study, training, preparation learning tools, micro and peer teaching, MoU, and curriculum change. Third, the forms of refreeze at MI Mambaul Ulum are a culture of quality, supervision and giving rewards and punishments. With this change management, it is expected that teachers at MI Mambaul Ulum can achieve indicators of teacher professionalism in the digital era.